Dada culture : critical texts on the avant-garde - Jones, Dafydd, 1965- (Avant garde critical studies, 2006)
"How Dada is to break its cultural accommodation and containment today necessitates thinking the historical instances through revised application of critical and theoretical models. The volume Dada Culture: Critical Texts on the Avant-Garde moves precisely by this motive, bringing together writings which insist upon the continuity of the early twentieth-century moment now at the start of the twenty-first. Engaging the complex and contradictory nature of Dada strategies, instanced in the linguistic gaming and performativity of the movement's initial formation, and subsequently isolating the specific from the general with essays focusing on Ball, Tzara, Serner, Hausmann, Dix, Heartfield, Schwitters, Baader, Cravan and the exemplary Duchamp, the political philosophy of the avant-garde is brought to bear upon our own contemporary struggle through critical theory to comprehend the cultural usefulness, relevance, validity and effective (or otherwise) oppositionality of Dada's infamous anti-stance"--